2,6-Dimercuriphenol as a Bifacial Dinuclear Organometallic Nucleobase - Ukale Dattatraya; Lönnberg Tuomas (Wiley - V C H Verlag GmbH & Co. KGaA, 2022)
A C-nucleoside having 2,6-dimercuriphenol as the base moiety has been synthesized and incorporated into an oligonucleotide. NMR and UV melting experiments revealed the ability of this bifacial organometallic nucleobase surrogate to form stable dinuclear HgII-mediated base triples with adenine, cytosine, and thymine (or uracil) in solution as well as within a triple-helical oligonucleotide. A single HgII-mediated base triple between 2,6-dimercuriphenol and two thymines increased both Hoogsteen and Watson–Crickmelting temperatures of a 15-mer pyrimidine·purine*pyrimidine triple helix by more than 10 oC relative to an unmodified triple helix of the same length. This novel binding mode could be exploited in targeting certain pathogenic nucleic acids as well as in DNA nanotechnology.